(untitled) (Orfeu, 2020)
When Leopoldo I was crowned emperor of the Holy Roman Empire in 1658, most of Europe was still in the process of economic recovery due to the so-called “general crisis of the 17th century”. Therefore, Leopoldo and the other members of the House of Habsburg were tasked with the reorganization and solidification of absolutism in the Austrian domains. To this end, the emperor found in sacred music an effective tool for convincing, advertising and displaying imperial power. This article aims to show the role of musical productions linked to the activities of the Counter-Reformation in Leopoldo I’s reign. Initially, will be examined Leopoldo’s religious education, as well as his particular interest in music and composition. There follows a discussion about the influence of the widowed empress Leonora de Gonzaga-Nevers (Leopoldo I’s stepmother) in the development of Austrian music, mainly in relation to her participation in the establishment of the sepulcro in Vienna.